Antimicrobial and synergistic activity of essential oils of Aloysia triphylla and Lippia alba against Aeromonas spp. (December 2017) - de Souza, Renilde Cordeiro; da Costa, Mateus Matiuzzi; Baldisserotto, Bernardo; Heinzmann, Berta Maria; Schmidt, Denise; Caron, Braulio Otomar; Copatti, Carlos Eduardo
Abstract: The objective of this study was to identify and quantify the chemical constituents, as well as the antimicrobial, antibiofilm and synergistic activity with florfenicol of essential oils of Aloysia triphylla (EOAT) and Lippia alba (EOLA) against Aeromonas spp. The antimicrobial activity of EOAT and EOLA was verified by the minimum bactericidal concentration (MBC) and the action against biofilm forming and consolidated biofilm. The synergistic activity of EOAT and EOLA with florfenicol was performed by the checkerboard technique. The main components of EOAT were α-citral (39.91%), E-carveol (25.36%) and limonene (21.52%), while that of EOLA was linalool (81.64%). Aeromonas spp. isolates showed sensitivity to both essential oils with MBC between 195.3 and 3125.0 μL/mL. Two isolates were classified as non-producing, three as moderate and 16 as weak biofilm producers. The EOAT and EOLA interfered in the biofilm formation, from moderate to weak producers, but did not cause any interference in the consolidated biofilm. The EOAT and EOLA combined with florfenicol showed synergistic effect and reduced MBC. The EOAT and EOLA have potential for application as antimicrobial agents, as they interfere in the initial formation of biofilm and when combined with florfenicol, present a synergic effect with a reduction in the minimum dose of the antibiotic. Highlights: Synergistic activity of essential oils with florfenicol was performed by checkerboard technique. Determination of chemical compounds of essential oils was carried out by GC-MS. The essential oils interfered in the biofilm formation, but did not in the consolidated biofilm. The essential oils had a synergistic effect with florfenicol, reducing the dose used. The efficacy of traditional antibiotics can still be improved.